The use of social media in orthopedic and trauma surgery education: a cross-sectional survey of german-speaking residents and medical students - Schmidt, Sebastian; Darwich, Ali; Leutheuser, Sebastian; Krahl, Daniel; Navas, Luis (Healthcare, 2024)
Background/Objectives: Social media has become a significant part of daily life, with platforms like Facebook and WhatsApp dominating usage. The COVID-19 pandemic further increased social media activity, including within the orthopedic community due to restrictions on physical gatherings. Despite the benefits of instant access to educational resources and interaction with experts, the lack of regulated editorial oversight on social media raises concerns about misinformation and privacy. This study aimed to evaluate the role of social media in orthopedic and trauma surgery education, focusing on platform use, user behavior, and engagement with educational content. Methods: A web-based survey was distributed to 912 residents and 728 medical students from the German-speaking Association for Arthroscopy and Joint Surgery (AGA) between June and July 2022. The questionnaire included 21 items covering demographics, platform use, activity patterns, engagement with educational content, and concerns about privacy. Results: Of the 339 respondents (129 medical students), 87% reported daily social media use, primarily via smartphones (93%). The most commonly used platforms were WhatsApp (84%), Instagram (68%), and YouTube (54%). About 26% of the content consumed was related to orthopedics or trauma surgery. While 70% engaged with specialist content by liking, commenting, or sharing, only 32% posted their own content. Additionally, 77% followed healthcare professionals or institutions, and 65% benefited from case presentations with images. Notably, 15% observed content that could violate patient privacy. Conclusions: Orthopedic residents and students are high-volume social media users but engage more passively with professional content. While most value educational material, concerns about privacy violations and inappropriate posts remain prevalent.